(untitled) (UNIHumanitas, 2019)
This research work addresses the linguistic attitudes and practices among public officials, in which the situation of the Guaraní language is described and analyzed in relation to the linguistic attitudes and practices of public officials in public institutions in the department of Itapúa. This study is considered important in order to know the situation of the Guarani language in the public administration, a fact that will help the competent authorities to make the most opportune decision for the strengthening of Guarani in its use and function based on the knowledge of the sociolinguistic reality of the population under study. With the objective of determining the linguistic attitudes and practices of the Guaraní language, this study was carried out based on a bibliographic review of the laws that support the inclusion of the Guaraní language in higher education, previous studies on linguistic attitudes and practices, and field work with the application of a questionnaire to officials who, because of their position, have direct contact with the people who come to their workplace. This work shows that public officials know that Guaraní is an official language alongside Spanish, understand that it is necessary to know and use it, and have a positive attitude towards this language and that the linguistic conduct of Guaraní should be strengthened.